Collision Induced Dissociation of PAHs and Biomolecules. (July 2015) - Giacomozzi, L; de Ruette, N; Gatchell, M; Stockett, M H; Schmidt, H T; Zettergren, H; Cederquist, H
Synopsis: We have performed an extensive set of experiments with focus on collisions between PAH or biomolecular cations and He atoms at center-of-mass energies around 100 eV. In this energy range, non-statistical fragmentation processes are important.